2019
DOI: 10.1177/0885066619840992
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Dose 4F-PCC Protocol for DOAC-Associated Intracranial Hemorrhage

Abstract: Purpose: Current guidelines favor 4F-PCC over plasma for reversal of warfarin. Uncertainty remains on the hemostatic effectiveness and thrombotic risk of 4F-PCC for direct-acting oral anticoagulants (DOACs), particularly in patients with intracranial hemorrhage (ICH). This study sought to evaluate the effectiveness and safety of a lower dose protocol of 25 units/kg 4F-PCC for the management of DOAC-associated ICH in a real-world setting. Materials and Methods: This was a retrospective study of adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
(56 reference statements)
4
39
0
Order By: Relevance
“…To our knowledge, there has been one head‐to‐head comparison of these two reversal strategies, but statistical analysis was not performed to compare effectiveness due to a limited sample size 18 . A plethora of single‐arm cohort studies of 4F‐PCC reversal for FXa‐associated bleeding have reported effectiveness rates of 69%‐95%, defined using the Sarode et al criteria or significant intracranial hemorrhage progression 25‐32 . The Sarode et al criteria were also used by most studies on real‐world use of andexanet alfa reversal 18‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been one head‐to‐head comparison of these two reversal strategies, but statistical analysis was not performed to compare effectiveness due to a limited sample size 18 . A plethora of single‐arm cohort studies of 4F‐PCC reversal for FXa‐associated bleeding have reported effectiveness rates of 69%‐95%, defined using the Sarode et al criteria or significant intracranial hemorrhage progression 25‐32 . The Sarode et al criteria were also used by most studies on real‐world use of andexanet alfa reversal 18‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen concentrate may decrease blood transfusion needs, multi-organ failure and mortality [100]. Reversal of vitamin K inhibition with four-factor prothrombin complex concentrate, at a dose of 25 U/kg IV, is promising for geriatric trauma patients, with or without intracranial haemorrhage, on warfarin or direct oral anticoagulant therapy [101][102][103][104].…”
Section: Pharmacologic Methodsmentioning
confidence: 99%
“…Given that simpler dosing regimens with PCC are emerging, this can lead to more timely administration, which may play a role in hemostatic efficacy success. 3 Finally, the authors do highlight the associated cost of both andexanet alfa and PCC. As mentioned previously, more emerging literature has found that 50 U/kg may not be required, and the authors' estimate of $5080 could in fact actually be $2540.…”
Section: Letter To the Editormentioning
confidence: 98%
“…The authors omitted a large portion of available effectiveness data associated with PCC use demonstrating hemostatic achievement rates as high as ~95% and as low 69%, which could skew readers’ bias toward andexanet alfa. 2,3 Second, the sample size studied was not robust (n = 352; only 249 were available for hemostatic efficacy assessment) and lacked high acuity patients, as indicated by the relatively low mortality rate (14%) compared with other reported oral anticoagulant–associated major bleeding mortality rates. 2,4 Also, with respect to safety and risk of development of thromboembolic events, the authors claim that andexanet alfa may be superior to PCC.…”
mentioning
confidence: 99%